Feasibility Analysis and Income Contribution of Banana Mulu Bebe Farming, West Halmahera District - Kaddas, Fatmawati; Ibrahim, Karmila; Baguna, Firlawanti Lestari (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2023)
Banana